Small UWB printed antenna with slotted ground plane - Khan R.A.; Chakrabarty C.K.; Ping L.C. (2023)
This paper presents an optimization design for the rectangular printed antenna with a slot ground plane for ultra wideband (UWB) application. A slot in the ground plane is shown to improve the bandwidth. The proposed antenna has a small size of 15 x 14.5 mm2. The design is on FR-4 substrate with dielectric constant of 4.4 and thickness 1.6 mm. Simulation is performed by using the CST Microwave Studio software. 2009 IEEE.